HUBUNGAN KARAKTERISTIK INDIVIDU DENGAN PENEMUAN KASUS TB PARU DI EKS KARESIDENAN PATI TAHUN 2013 - Emaliana Saomi, Eva; Cahyati, Widya Hary; Indarjo, Sofwan (Unnes Journal of Public Health, 2015)
Pulmonary TB cases are increasingly found every year. The objective this study was find out the correlation between individual characteristic toward the finding pulmonary TB cases in ex Pati Residency during 2013.It was analytical survey research using case control approach. 15 persons in each case and control group were taken as sample using simple random sampling technique. The data was analyzed using chi square test with degree of significance (α)=0,05.The research result showed that the risk factor correlate with the finding of pulmonary TB cases were education background (p value=0,027, OR=8,00), knowledge (p value=0,023, OR=9,75), and training (p value=0,023, OR=9,75). Variables which uncorrelated were age (p value=0,264), gender (p value=0,449), duration of employment (p value=0,245), and officers’ behavior (p value=0,053). Advice for health department in ex Pati Residency for the officers’ who was educated in high school in order to proceed to the level of D3/S1. For other researchers study more theother factors associated with individual characteristics against pulmonary TB case finding.